2016
DOI: 10.1186/s12882-016-0388-2
|View full text |Cite
|
Sign up to set email alerts
|

Relation of peritubular capillary features to class of lupus nephritis

Abstract: BackgroundExperimental studies have linked peritubular capillary (PTC) loss with progression of chronic kidney disease. Minimal information on PTC in lupus nephritis (LN) has been reported. We therefore evaluated the PTC area in different classes of LN and determined if specific clinical characteristics correlated with PTC changes.MethodsRenal biopsies of 253 subjects with LN (categorized using the ISN/RPS 2003 classification) and 13 normal renal donors (the controls) were retrospectively evaluated for PTC mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Regardless of initial insults, chronic injuries to the kidney frequently induce tubular atrophy, fibrosis, inflammation and peritubular capillary (PTC) rarefaction (Figure 1). PTC rarefaction is identified not only in diabetic nephropathy and hypertensive kidney diseases, two major causes of CKD [4][5][6], but also in advanced IgA nephropathy [7], congenital nephrotic syndrome [8], lupus nephritis [9], polycystic kidney disease [10,11], and allograft nephropathy [12,13], suggesting that PTC loss is a very common event in patients with CKD. Interestingly, the aging process itself accelerates PTC rarefaction [14].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of initial insults, chronic injuries to the kidney frequently induce tubular atrophy, fibrosis, inflammation and peritubular capillary (PTC) rarefaction (Figure 1). PTC rarefaction is identified not only in diabetic nephropathy and hypertensive kidney diseases, two major causes of CKD [4][5][6], but also in advanced IgA nephropathy [7], congenital nephrotic syndrome [8], lupus nephritis [9], polycystic kidney disease [10,11], and allograft nephropathy [12,13], suggesting that PTC loss is a very common event in patients with CKD. Interestingly, the aging process itself accelerates PTC rarefaction [14].…”
Section: Introductionmentioning
confidence: 99%
“… 34 , 35 , 37 40 , 42 The observation that PTC rarefaction is associated with disease progression and age has also been validated in a variety of other human kidney diseases. 26 52 , 55 …”
Section: Discussionmentioning
confidence: 99%
“…Building on these observations 26 55 and leveraging the rich NEPTUNE dataset 13 and powerful image analysis tools, 11 , 12 , 21 we extracted selective PTC quantitative features, including density, size, and aspect ratio, from DL-derived PTC segmentations and assessed their associations with disease progression. We demonstrated that the shape of PTCs is a previously unrecognized biomarker of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence to show that peritubular capillaries play an important role in CKD and are a key regulator of CKD progression [39]. Peritubular capillary rarefaction is found not only in diabetic nephropathy [40] and hypertensive nephropathy [41], but also in IgA nephropathy [42], congenital nephrotic syndrome [43], lupus nephritis [44], and polycystic kidney disease [45]. Thus, protecting peritubular capillaries is a crucial approach to alleviating renal brosis [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%